dick francis : field of thirteen - Francis, Dick; Dick Francis (New York Berkley publishing group, 1998)
Field of Thirteen by Dick Francis is a collection of thirteen suspenseful short stories centered on the world of horse racing, murder, and mystery. These stories, often featuring themes of revenge, showcase tightly plotted tales of jockeys, owners, and trainers, including stories of an Australian stud farm owner investigating a doping scandal
English